Renal Resistive Index as a Novel Indicator for Renal Complications in High-Fat Diet-Fed Mice - Hairong Xu; Zejun Ma; Shan Lu; Rui Li; Liangkun Lyu; Lexi Ding; Qiulun Lu (Karger Publishers, 2017)
Background/Aims: The renal resistive index (RI) is a novel candidate as a renal injury prognostic indicator, but it remains unclear how renal RI levels correspond to renal injury in diabetic nephropathy. Methods: To examine this issue, we compared 8-week-old male C57BL/6 mice fed with high-fat diet (HFD) versus chow diet (CHD) for 16 weeks. At 8 and 12 weeks, the glomerular filtration rate (GFR), urinary albumin-to-creatinine ratio (UACR), and inflammatory factors (IL-1β, IL-6, TNFα, and MCP-1) were measured, along with the increase in renal RI. Results: Our study suggests RI values positively correlate with GFR for the first 12 weeks of HFD feeding. In contrast, the GFR of 16-week HFD feeding is lower than that of 12-week HFD feeding, whereas RI levels are significantly increased. Additionally, our study suggests RI values accurately indicate the renal fibrosis and renal injury in HFD-fed mice treated with lovastatin. Conclusion: This study seems to confirm the utility of a noninvasive and repeatable ultrasound parameter to rapidly evaluate renal fibrosis in a HFD-induced type 2 diabetic mouse model in vivo. This highly sensitive and comparable renal RI measurement could monitor the whole procedure of disease development in real-time. RI measurement of the renal artery is capable of differentiating responses to standard therapy with lovastatin in HFD-fed mice from the CHD group.